Workshop Pembuatan Penelitian Tindakan Kelas bagi Guru Sekolah Dasar di Kecamatan Barabai Kabupaten Hulu Sungai Tengah - Radiansyah Radiansyah; Fathul Jannah; Raihanah Sari (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
Making Classroom Action Research (CAR) for teachers at SD, Barabai District, Hulu Sungai Tengah Regency, South Kalimantan. The methods used in this research are lectures, discussions, and training which are carried out through webinars using the Zoom application. The community service participants are 36 teachers from elementary schools in Barabai District, Hulu Sungai Tengah Regency. The training activities went well and received positive responses from the teachers. This activity has a positive impact on the ability of teachers in terms of knowledge and self-development related to making CAR.